Architecture, urbanism, construction work and local labor at the turn of the 20th century in Lourenço Marques, Mozambique - Mendonça, Lisandra Franco de (2021)
In the last 15 years, substantial research has been conducted on architecture and urbanism in African Portuguese speaking countries, scrutinizing the introduction and influences of design and planning throughout the late 19th and 20th centuries.The social sciences literature on the five postcolonial states, especially since the 1990s, helped with investigating the legacy of these mechanisms in maintaining colonial power and knowledge post-independence. Construction history has paid scant attention to the architectural production in that context. However, much can be gained to understand when and how racialized categorizations of materials and construction technologies were introduced; and how labor involving local workers was organized. To illustrate this claim, use will be made of documentation produced by the PublicWorks Office from the late 19th and first decades of the 20th centuries concerning Lourenço Marques, available at the Portuguese Overseas Historical Archives and at the Historical Archive of Mozambique.